The Data Package in Learning Mean Using LSLC and PMRI - Poppy Trianti Rahayu; Ratu Ilma Indra Putri (Jurnal Pendidikan Matematika, 2021)
This study aims to produce statistical learning designs in the introduction of the concept of average values and knowing student learning outcomes in learning average values by previously learning about the presentation of data consisting of tables and diagrams through learning trajectories and what happens during the learning process. This learning is based on Lesson Study for Learning Community (LSLC), the approach of Indonesian Realistic Mathematics Education (PMRI). This study uses a type of Design Research method research design type of validation study, which involves in MTs 1 in Palembang. There are three stages in design research type validation studies namely Preparing for the experiment in the form of literature study and the design of the Hypothetical Learning Trajectory (HLT); Design experiment in the form of a Preliminary Teaching Experiment (Pilot Experiment) and Teaching Experiment; and Restrospective analysis. The instruments used were written test, video and field notes. The results of learning experiments show that the design of learning provided has helped students understand the concept of Mean.